Cover Image: Volume 1 Issue 3. Issue 3 (11th October 2022) - Unknown
Abstract : Applied Research presents high‐quality peer‐reviewed research from diverse backgrounds across the physical and life sciences. The journal is aimed at the intersection of academia and industry, and bridges the gap between fundamental studies and applications of ideas, methods, instrumentation, and novel engineering.